Governance, Empowerment and Benefits of Co-Management of Inland Open Water Fisheries in Bangladesh - Kabir, Golam Md. Shamsul (2009)
The main objective of the study is to assess co-management approaches as institutional arrangement of inland openwater fisheries in Bangladesh. It was done by examining the factors enhancing the governance and empowerment of fishers for improved arrangements of fishers’ and co-management based organisations’ (CBOs. The benefits of co-management approaches on income and transaction costs of fisher communities are examined and the effectiveness of conflict mitigation and resolution are compared. A survey of 311 fishing households in Bangladesh was conducted from July 2008 to October 2008 to obtain information from fishers in the Community Based Fisheries Management (CBFM) project sites and non CBFM sites (control sites) using structured interview questionnaire. The CBFM approaches aim mainly at building local fishery community organizations for managing fisheries sustainably and to improve institutional arrangements of fisher communities. Institutional arrangements have been done through formation of local co-management based organisations which have led to increased democratic participation, empowerment, enhanced fisheries management and better compliance of rules and regulations. Descriptive analysis, Factor analysis and finally Regression analysis are used to analyse the data. The results of the study reveal that the fishers of CBFM sites have increased participation in collective decision-making, improved leadership, trust, decentralisation of management, power sharing responsibility and social networks which have led to improve governance of the fisher communities. The study shows that the fishers and CBOs are more empowered due to training in skill development and capacity enhancement and awareness raising programs facilitated by the Government and NGOs. In addition, they have greater individual access rights to their fisheries through administrative support from the government and they are more capable of controlling the exploitation of fisheries resources in project areas. All these factors have made the CBOs more accountable and transparent. The results also indicate that there are improvements in compliance and legitimacy and lowering of transaction costs. The study shows that conflicts are resolved quickly and conflict management process is smooth in project sites compared to non CBFM control sites. The results of the study show that there is significant difference in total transaction costs in management between project and control sites over the years. The transaction costs trended downward within project sites, but it is increasing in control sites.